Analisis Pestel Dan SWOT Sebagai Dasar Perumusan Strategi Pada PT. Asrinda Arthasangga Reinsurance Brokers - Istichanah Istichanah (ARBITRASE: Journal of Economics and Accounting, 2022)
Reinsurance brokerage business is a consulting and/or intermediary service business in placing reinsurance or sharia reinsurance placement and handling claims settlement by acting for and on behalf of insurance companies, sharia insurance companies, guarantee companies, sharia guarantee companies, reinsurance companies, or sharia reinsurance companies that place reinsurance or sharia reinsurance. This study aims to determine what are the external and internal environmental factors of the company at PT. Asrinda Arthasangga Reinsurance Brokers, then carried out an analysis of these factors using PESTEL and SWOT analysis as a basis for formulating a strategy that will be used by the company so that it is more advanced and developed so that the vision, mission and goals of the company are achieved. This study uses a qualitative method using the research object is PESTEL and SWOT analysis and the research subject is PT. Asrinda Arthasangga Reinsurance Brokers. The results of research using PESTEL and SWOT analysis show that PT. Asrinda Arthasangga Reinsurance Brokers is in quadrant 1 or the position of growth and development (growth). The strategy that must be implemented is a strategy that supports an aggressive growth policy. PT. Asrinda Arthasangga Reinsurance Brokers formulates both short term and long term strategic plans. The short-term strategy is in the form of a functional strategy which is a short-term activity within the company that must be developed by each function area of the company to implement corporate strategy and business strategy in each department or section.